THE EFFECT OF CUSTOMER TRUST AND CUSTOMER EXPERIENCE TOWARDS REPURCHASE INTENTION IN IGOR’S BAKERY SURABAYA - Taralyn, Felyna; Susilo, Clarissa Listya; Hendra (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This research was conducted with the goal of examine and test the influence of customer trust and customer experience towards repurchase intention in Igor’s bakery. This research uses a quantitative research method and SPSS to analyze the data. Based on the data analysis that was done, it can be concluded that customer trust as well as customer experience has a partial significant influence towards repurchase intention and both customer trust and customer experience has a simultaneous influence towards repurchase intention.